Modification of the surface of copper alloys with aluminum in the conditions of self-propagating high-temperature synthesis - Sereda, B.; Kryhliyak, I.; Sereda, D.; Kryhliyak, D. (Problems of Atomic Science and Technology, 2023)
The influence of the technological parameters of the SHS process (temperature, holding time and alloying of B, Cr, Ti) on the corrosion resistance of brass with a surface alite layer, which effectively resists β-radiation, was studied. The research was carried out in 30% aqueous solutions of HNO₃, HCl, H₂SO₄. Aluminized coatings doped with silicon, which are obtained under optimal parameters, have 1.7-2.1 times higher corrosion resistance than doped B and Ti. Alloyed coatings have phases CuSi, CuAl, CuAl₂, CuTi, Ti₂Cu₃, CuCr, Cu₃Al, Cu₂Al, Al₃Si, and α-phase doped with Cr, Al, Si, B, Ti. When tested in a 30% aqueous solution of nitric acid, the coating doped with titanium and silicon shows a weight loss of 32 and 37 g/m², respectively.